Empowering Women for a Prosperous Household: Amplifying Family Income through Economic Empowerment - Milania, Yolanda; Dwi Saputra, M Reza (Women, Education, and Social Welfare, 2024)
Presented as a case study, this qualitative inquiry seeks to provide an overview of the outcomes of the Ecoprint business-driven women's economic empowerment program in Metro City. This study delves into the pivotal role of women's economic empowerment in augmenting household income and overall prosperity. Data collection encompassed interviews, observations, and documentation, facilitated by non-test instruments such as interview, observation, and documentation guidelines. The collected data underwent qualitative descriptive analysis, enhanced by source triangulation for validity. This analytical process involved data reduction, presentation, and conclusion drawing. The findings show how the women's economic empowerment program transforms housewives from home-bound roles to empowered women contributing to family finances through skills like crafting Ecoprint and Shibori fabrics. This shift results in heightened family income. This research underscores the potential for empowering housewives to uplift family economies, underscoring the significance of such opportunities for improved household prosperity.